2020
DOI: 10.1002/mma.6705
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid flow through microchannel with a triangular corrugated wall: Heat transfer enhancement against entropy generation intensification

Abstract: In the present study, the effects of applying magnetic field on heat transfer and entropy generation of a nanofluid through microchannel with a triangular corrugated wall were examined. Considering the slip velocity, the effects of Reynolds and Hartmann numbers on the Nusselt and Bejan numbers have been studied. The positive effect of installing triangular ribs is increase in the heat transfer area, but the negative effect corresponds to vortex formation at high Reynolds. Applying magnetic field diminished the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The local Nusselt number varies in a periodic way over the length of the microchannel and rises with the growth in the Reynold number, according to the findings. Nguyen et al [ 140 ] analyzed the impacts of the magnetic field in a slippery microchannel. Applying a magnetic field to the microchannel enhanced both slip velocity and temperature gradient close to the wall, according to the findings.…”
Section: Introduction To Microstructuresmentioning
confidence: 99%
“…The local Nusselt number varies in a periodic way over the length of the microchannel and rises with the growth in the Reynold number, according to the findings. Nguyen et al [ 140 ] analyzed the impacts of the magnetic field in a slippery microchannel. Applying a magnetic field to the microchannel enhanced both slip velocity and temperature gradient close to the wall, according to the findings.…”
Section: Introduction To Microstructuresmentioning
confidence: 99%
“…Also, they found that at higher Reyonlds number, the periodic flow could transition to nonperiodic or chaotic flow due to instabilities. Nguyen et al 22 numerically studied the nanofluid flow through a microchannel with triangular corrugated wall. The heat transfer is augmented due to the corrugation, which also significantly increases entropy generation caused by vortex generation, and this can be mitigated by applying a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Rising the mean Nu number and entropy generations in all Re numbers was a clear outcome of rising the percentage of nanofluid volume fraction. Nguyen et al (2020) used triangular ribs as vortex generators and hybrid nanofluids to increase the heat transfer. The outcomes of simulation claimed that the heat transfer can be achieved at higher nanofluids in the presence of triangular ribs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, heat transfer increments with increasing Reynolds number and wingchord ratios. Nguyen et al (2020) and employed a wavy wall to make vortexes to improve heat transfer in a heat exchanger by hybrid nanofluids. According to their outputs, as the amplitude of wave rises, the strength of vortexes turns higher and results in more heat transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation